Maritime Security Diplomacy Facing the Threat of Pollution and Environmental Damage to Realize Golden Indonesia 2045 - Mulyaningrum, Retno; Wiranto, Surya; Saragih, Herlina Juni Risma; Ali, Yusuf; Suwarno, Panji; Widodo, Pujo; Syahtaria, Moh Ikhawan (PT FORMOSA CENDEKIA GLOBAL, 2024)
Research analysis with qualitative methods that explain the relationship between the theory of maritime diplomacy and maritime security in the discussion. The correlation of Indonesian environmental law and international environmental law in the understanding between countries which is the basis for acting between countries so that there are safe limits and do not violate international or domestic Indonesian agreements. The discussion refers to the development of maritime diplomacy by analyzing the threat of pollution and environmental damage experienced by Indonesia. The results of research that takes environmental problems including pollution, wastewater that have occurred provide an overview of the threat of pollution and environmental damage that can arise from various sources, including pollution, climate change, deforestation, and unsustainable exploitation of natural resources.